The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.5172/ijpl.5.2.80
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Computer-Assisted Language Learning in the EFL Classroom: Teachers’ Perceptions and Perspectives

Abstract: The aims of the study reported in this article are to investigate factors affecting English as a foreign language (EFL) teachers' use of computers in their classrooms and to find out EFL teachers' perceptions of computer-assisted language learning (CALL) and ways to improve CALL practice in school settings. Participants in the study were twelve Korean in-service teachers of EFL working at secondary schools in Korea. A questionnaire and follow-up in-depth interviews were employed to collect data. The results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(51 citation statements)
references
References 11 publications
5
32
0
Order By: Relevance
“…However, some studies have indicated that technology integration by teachers in the classroom is insufficient (Ertmer, 1999;Ertmer, 2005;Park & Son, 2009). This observation has led to analyses of technology integration by teachers (Gülbahar, 2007;Güyer & Sahin, 2011;Jang, 2008;Liu,2009), and also hints at the affordability and constraints of technology as an enabler of different teaching approaches (Mishra & Koehler, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have indicated that technology integration by teachers in the classroom is insufficient (Ertmer, 1999;Ertmer, 2005;Park & Son, 2009). This observation has led to analyses of technology integration by teachers (Gülbahar, 2007;Güyer & Sahin, 2011;Jang, 2008;Liu,2009), and also hints at the affordability and constraints of technology as an enabler of different teaching approaches (Mishra & Koehler, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the diverse picture of language teachers' computer literacies, most research illustrates that a large proportion of language teachers consider CALL implementation beneficial for their instruction (Albilirini, 2006;Aydin, 2013;Bordbar, 2010;Li & Walsh, 2011;Park & Son, 2009;Yunus, 2007).…”
Section: Language Teachers' Attitudes and Beliefs About Call Usementioning
confidence: 99%
“…Previous research exploring language teachers' computer literacy skills has been conducted in Asia (Albilirini, 2006;Aydin, 2013;Chen, 2012;Li & Walsh, 2011;Park & Son, 2009;Shin & Son, 2007;Son, Robb, & Charismiadji, 2011;Sumi, 2010;Yunus, 2007), Europe (Dooly, 2009;Fuchs, 2006), North America (Fuchs & Akbar, 2013;Kessler & Plakans, 2008;Lam, 2000;Meskill, Anthony, Hilliker-Vanstrander, & You, 2006;Wiebe & Kabata, 2010), and South America (Barsotti & Martins, 2010). It has been demonstrated that increased access to technology facilities does not guarantee that language teachers would always integrate CALL into their instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, teachers' lacking computer literacy in most countries constitutes a major impediment in this regard. Studies have indicated that although many teachers often use technology in their daily lives, they do not apply it in class (Cuban, 1993;Ertmer, 2005;Park & Son, 2009;Wang, 2007). Furthermore, studies have claimed that even if schools provided adequate hardware and software, many teachers would still follow the traditional way of teaching (Mumtaz, 2000).…”
Section: Introductionmentioning
confidence: 99%